Inﬂuence of dynamics viscosity on the water base CNTs nanofluid flow over a stretching surface. Issue 1 (1st January 2020) - Rehman, Ali; Salleh, Zabidin; Gul, Taza
Abstract: This research paper explains the impact of dynamics viscosity of carbon nanotubes (CNTs) water base nanofluid for different parameter for both velocity and temperature profile. Similarity transformation is used to convert the partial differential equation to nonlinear ordinary differential equation. The solution of the problem is obtained using the optimal homotopy analysis method. The stability of the problems is also obtained up to the 30th order approximation using the BVPh 2.0 package. The outputs are displayed and discussed. The effects of various parameters on the skin friction coefficient and Nusselt number coefficient of single and multi-walled CNTs are displayed and discussed.